Depression and Deliberate Self-Harm Among Rural Adolescents of Sichuan Province in Western China: A 2-Year Longitudinal Study - Lai, Shimin; Su, Chang; Song, Shasha; Yan, Mingxia; Tang, Chengmeng; Zhang, Qiang; Yin, Fei; Liu, Qiaolan (Frontiers in Psychiatry, 2021)
Objective: Depression and deliberate self-harm (DSH) are common psychological and behavioral problems among adolescents. Methods: A total of 2744 junior and senior high school students from two rural schools in Sichuan Province, China, participated in the baseline survey and were invited to participate in two follow-up surveys. The Center for Epidemiologic Studies-Depression Scale, a deliberate self-harm item, the Social Support Rating Scale, the Rosenberg Self-esteem Scale and the Connor-Davidson Resilience Scale were administered. A bivariate four-level logistic regression model was used for analysis. Results: The prevalence of depression and deliberate self-harm were 39.6% and 21.2%, respectively. Regular physical exercise, a good relationship with parents, high resilience, and high self-esteem were common protective factors for both depression and deliberate self-harm. Feeling disliked by teachers was a common risk factor for both. Being female, having a mother who emigrated as a migrant worker before the student was 3 years old, feeling disliked by classmates and having a poor family economic status were associated only with an increased risk of depression. Participants with medium social support were less likely to report deliberate self-harm than those with low or high support. Depression and deliberate self-harm were clustered at the class level. Conclusions: The comorbidity of depression and deliberate self-harm in rural adolescents should be given ample attention. Interventions should consider the class clustering of depression and deliberate self-harm and their common and unique influencing factors.